University vocational training under conditions of informatization - V. V. Laptev; T. N. Noskova (Высшее образование в России)
Formation of the modern professional competencies of graduates and their personal qualities corresponding to the challenges of the information society refers in the article to the innovative quality of university training. It is shown that organization of extracurricular independent work has a specific role in the process of formation of student’s advanced features and qualities in university education environment. This work should be organized through e-technology network environment interactions. The implementation of the promising models of educational activity in this environment creates a prerequisites for forming student’s individual educational way, that corresponds to the requirements of the Bologna process.New forms of information flow processes offer the opportunities of innovative student development through the promotion of his self-actualization in a scalable electronic environment.